Influencia de los porcentajes de agente endurecedor y tiempo de esterilización en la calidad de pitahaya (Hylocereus undatus) en almíbar - Ormaza Cevallos, Angela Yomira (2024)
The objective of this research was to establish the influence of hardening agent percentages and sterilization time on the physicochemical properties and sensory preference of pitahaya in syrup. A bifactorial AXB arrangement was applied, considering six treatments with three replicates, resulting in 18 experimental units. The results for pH and titratable acidity were analyzed using the parametric test (ANOVA), while color and texture were analyzed using the non-parametric test (Kruskal-Wallis). Factor A (Calcium chloride percentages) at its level a2 (0.3% CaCl2) influenced the titratable acidity variable, providing the best average with a value of 0.22%. Factor B (Sterilization time) at its level b3 (30 min) yielded the best pH and titratable acidity means for the preserve, with values of 5.34 and 0.23%, respectively. For the texture profile, levels b1 (20 min) and b2 (25 min) provided the best textural characteristics. Sensory analysis (preference ranking) was conducted by 75 untrained panelists, and the results were analyzed using the Friedman test. The untrained panelists showed significant differences between treatments. Treatments T4 and T1 ranked in the first subset with the lowest average ranks, indicating that the best combinations of levels were 0.3% CaCl2 + 25 minutes of sterilization and 0.1% CaCl2 + 20 minutes of sterilization, which likely provided the best textural characteristics to the preserve, an attribute that could have been crucial during the sensory test.